(untitled) (Veterinária Notícias, 2019)
The study was conducted aiming to evaluate three commercial strains of broiler chickens about their production performance and carcass yield up to 42 days of age. Three thousand day-old chicks were alocated in a randomized 3x2 factorial design, with three commercial strains (Ross AP95, Cobb e Hubbard) and two sex, with ten replicates per treatment. The chicks were distributed in 60 metal boxes of 1,58m x 2,61m x 0.7m. At 42 days a bird per box was identified and send to slaughter house, totaling 60 birds, to evaluate the 2003carcass yield. The commercial strains Cobb and Hubbard did not differ for the average weight parameters, gain mean weight, productive efficiency index and daily weight gain, with statistically superior results to the commercial strain Ross. To feed conversion, commercial strain Hubbard showed statistically similar results to the Cobb, which in turn was statistically equal to the commercial strain Ross. For the income of chicken cuts the three commercial strains did not differ. For the yield of thigh, drumstick and abdominal fat there was a significant difference between male and female sex.